The Rate of Seller Correctness in Naming Batik Solo Pattern: Studied in Indonesia Online Marketplace - Lidiawaty, Berlian Rahmy; Irawan, Mohammad Isa; Ginardi, Raden Venantius Hari (Jurnal Sosial Humaniora, 2025)
Every pattern in batik Solo has a different meaning that affects its use. There are patterns for cultural ceremonies, including funerals. Therefore, the seller of batik Solo’s product has to be able to give the right title as the name of its product in the online marketplace, so the customer will not miss wear the batik in the wrong ceremony. According to the importance of naming batik Solo’s product, this study aims to assess the accuracy of batik Solo pattern naming by sellers in Indonesian online marketplace. Thus the result of it can be used by the buyer as a recommendation where is the best marketplace to purchase the batik Solo product. First, the study collects the images sample from four biggest marketplaces in Indonesia; Tokopedia, Bukalapak, Shopee and Lazada. The sample was collected by inputting the name of batik Solo pattern in the marketplace’s search bar. The keywords that have been used to collect the sample are batik Parang, batik Truntum, batik Sawat, batik Kawung and batik Slobog. Those are the kinds of batik Solo pattern that has different expedience from each other. After 834 samples have been collected, the study assigns whether the seller give the correct name to the batik Solo product or not. The result of this study is the correctness percentage (CP) of the seller in naming their batik Solo product. In general, the CP is 82,13%, Marketplace with the highest CP is Lazada (95,42%) and the highest CP of pattern is Parang (91%). Besides that, the study also rates marketplace with the parameter of Best Marketplace by Pattern (BMP) and Best Marketplace of Category (BMC). The study divided the parameters to rate marketplace because the best marketplace that has the highest correctness percentage in one category of a pattern is not always a marketplace that has the highest correctness percentage in that pattern.